Effectiveness of syrup paico (Chenopodium Ambrosioides) in 6 to 10 years with intestinal parasites - Esteban-Robladillo, Isabel (2019)
The research "Effectiveness paico syrup (Chenopodium ambrosioides) in children / as of 6-10 years intestinal parasitosis in intercultural community Bilingual" Bena Jema "April - September 2012", worked with the aim of determining the effectiveness of syrup of paico in girls aged 6-10 years intestinal parasitosis; the methods used were analytical-synthetic, inductive-deductive method and the explanatory method arriving at the following results: When administering paico syrup 12 parasitized parasite load more children at a dose of 4 mL for two days and to take samples taken post found that persisted and eliminating parasitic load was minimal; to administer 10 ml for ve days syrup paico 12 parasitized children with higher parasite burden and make the post show takes was found to have greater deworming which leads to the conclusion: paico syrup administered to children and aged 6 to 10 years at a dose of parasitized 10ml unlike is effective rate of 4 ml in eliminating intestinal parasites. (As Ascaris lumbricoides and protozoa).